Apakah Korupsi Merupakan Salah Satu Budaya Di Indonesia (Studi Kasus Di Dusun Sena Baru, Desa Kuta Paret, Kecamatan Selesai, Kabupaten Langkat ) - Sibuea, Mashrul Zuhri; Fauziah, Alvina; Azhara, Arindi Safina; Arizky, Atika; Khairunisa, Sheika Sarah; Ningsih, Nabilla Widya; Putri, Alya Nabila (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study explores whether corruption can be considered a cultural phenomenon in Indonesia, focusing on a case study in Sena Baru Hamlet, Kuta Paret Village, Selesai Subdistrict, Langkat Regency. A qualitative method with a case study approach was employed, using in-depth interviews, participatory observation, and document analysis. Findings indicate that while corruption has not fully become an inherited tradition like customary values, it is increasingly accepted within certain social contexts. Factors such as low transparency, weak social oversight, and kinship ties are among the key drivers of corrupt practices at the village level. Furthermore, some community members view corruption as a natural consequence of holding public office or as repayment for support received. Despite this, there remains potential to prevent corruption from becoming deeply rooted through anti-corruption education, strengthening the role of religious figures and youth groups, and improving local governance structures.